The Primacy-of-Warmth Effect on Spontaneous Trait Inferences and the Moderating Role of Trait Valence: Evidence From Chinese Undergraduates - Zhang, Qing; Wang, Meifang (Frontiers in Psychology, 2018)
Research has showed that warmth and competence are the fundamental content dimensions underlying social judgment, and warmth judgments are primary. However, overwhelming majority of research concerning “primacy-of-warmth” rests on traits judgment or lexical recognition, and little attention has been paid to spontaneous trait inferences (STIs) that are made on exposure to trait-implying behaviors. Two studies were performed to examine the primacy-of-warmth effect on STIs, and to further explore whether traits' valence moderates the effect. Consistent with our expectations, the results of Experiment 1 and 2 (for spontaneous trait activation and spontaneous trait binding, respectively) consistently demonstrated the primacy-of-warmth on STIs. Participants were more likely to draw STIs from behaviors implying warmth traits than those implying competence traits. Moreover, the primacy-of-warmth effect on STIs was moderated by the traits' valence. In concrete terms, participants were more likely to draw STIs from negative warmth behavioral sentences than negative competence behavioral sentences, whereas participants draw STIs from positive warmth behavioral sentences and from positive competence behavioral sentences equally. An original contribution made by our study is that we obtained the primacy-of-warmth effect on STIs, providing further evidence for primacy-of-warmth effect in domain of implicit social cognition. Keywords: spontaneous trait inferences, spontaneous trait activation, spontaneous trait binding, primacy-of-warmth, valence, warmth, competence